2006
DOI: 10.1002/hed.20534
|View full text |Cite
|
Sign up to set email alerts
|

Screening for local and regional cancer recurrence in patients curatively treated for laryngeal cancer: Definition of a high‐risk group and estimation of the lead time

Abstract: Risk profiles for locoregional relapse were defined. Intensifying the follow-up schedule is not advisable because the lead time is very short. An excessively high number of routine visits would have to be performed to increase the detection rate for asymptomatic recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…These findings are consistent with previous studies demonstrating histologic tumor grade as a powerful predictor of distant metastasis, adding important information to clinical and pathologic neck staging, including consideration for systemic treatment [16]. Histologic grade also emerged as a significant risk factor of local or regional laryngeal cancer recurrence [17]. The 1998 National Cancer Data Base (NCDB) Report on Cancer of the Head and Neck [9] reported that poorly differentiated head and neck cancers were most notably associated with advanced stage.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with previous studies demonstrating histologic tumor grade as a powerful predictor of distant metastasis, adding important information to clinical and pathologic neck staging, including consideration for systemic treatment [16]. Histologic grade also emerged as a significant risk factor of local or regional laryngeal cancer recurrence [17]. The 1998 National Cancer Data Base (NCDB) Report on Cancer of the Head and Neck [9] reported that poorly differentiated head and neck cancers were most notably associated with advanced stage.…”
Section: Discussionsupporting
confidence: 90%
“…This study challenges the belief that routine surveillance improves survival after laryngeal cancer recurrence. Consistent with previous reports,11, 12, 25 there was no difference in overall postrecurrence laryngeal cancer survival based on surveillance intensity. However, in subsite analysis, a survival advantage was apparent for patients with recurrent glottic cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Cross‐reference checking revealed no additional relevant articles. A total of 12 articles were selected for study assessment …”
Section: Resultsmentioning
confidence: 99%
“…Twelve articles were assessed for their relevance and risk of bias . Nine articles were characterized by a high relevance and the other 3 studies by a moderate relevance. The follow‐up duration or time interval in determining recurrence was unknown in 2 studies .…”
Section: Resultsmentioning
confidence: 99%